Empirical Analysis of Remittance Inflow: The Case of Nepal - Thagunna, Karan Singh; Acharya, Saujanya (International Journal of Economics and Financial Issues, 2013)
This paper analyzes the nine year remittance inflow and macroeconomic data of Nepal, and studies the effect of remittance on each of those macroeconomic variables. We have used Unit Root Test, Least Squared Regression Analysis, and Granger Causality Test. The empirical results suggest that remittance has more causality on the consumption pattern as well as the import patter, and less on investments. Furthermore, with available literatures, this paper discusses the importance of channeling the remittance funds into the productive capital, mainly the public infrastructure, in comparison with the South Korean case study. Keywords: Remittance; Growth; Unit Root Test; Granger Causality Test; Cobb-Douglas Function; Two Gap Model; Nepal JEL Classifications: E13; E22; F24; O40